جدید مغربی علوم پر نقد و استدراک اوراخذ و استفادہ: مسلم مفکرینِ تعلیم کی آراء کا تجزیاتی مطالعہ: Criticism and Reparation of Contemporary Western Sciences & Derivation and Utilization: Analytical Analysis of the Views of Muslim Intellectuals - Sarfraz Husain Saeed; Dr. Arshad Muneer (MEI, 2023)
Knowledge belongs to various fields, which dicuss the social, political, natural and material aspects of any society. Basically, there are two theories about knowledge; Islamic Theory and Secular or Western Theory. These theories reflect the social background of any society. Ethical values carry primary importance in educational system. With their development, contemporary Westren sciences have laid huge impact on not only non-muslim individuals, but some muslim intellectuals have also fallen prey to their sententious impact. In result, muslim scholars feel proud after getting educated from Westren sciences. But, being devoid of spiritual impact, Western sciencs have led them to the way where neither God has any place nor the ethical values have any importance. Since the importance of Western sciences, in current scenario, cannot be denied, the muslim scholars and intellectuals have shown serious concern in this matter. They have different view points on whether the muslims should derivate and utilize the contemporary Western sciences or not. There has been a lot of debate and discussion on the issue of Islamization of modern Western sciences among the muslim intellectuals also. This article aims to analyze the views of muslim intellectuals on derivation and utilization from Western sciences and also the discussion will be made on how the unislamic elements of western sciences can be Islamized.